Complex Analysis of the Necessary Geometric Parameters of the Tested Component in the Ring-Core Evaluation Process - Šarga, Patrik; Galajdová, Alena; Vagaš, Marek; Menda, František (Measurement Science Review, 2022)
Residual stress measurement in different sorts of mechanical and mechatronic objects has become an important part of the designing process and following maintenance. Therefore, a sufficient experimental method could significantly increase the accuracy and reliability of the evaluation process. Ring-Core method is a well-known semi-destructive method, yet it is still not standardized. This work tries to improve the evaluation process of the Ring-Core method by analyzing the influence of the necessary geometric parameters of the investigated object. Subsequently, residual stress computation accuracy is increased by proposed recommendations.